Pemberdayaan Ibu Balita dalam Mengenali dan Mencegah Diare di Desa Bangun Rejo, Tanjung Morawa, Deli Serdang, 2025 - Retno Wahyuni; Febriana Sari; Edi Subroto; Rolasnih Lilista Simbolon; Sitti Nuraisyah; Yuni Efitasari; Yosefvania Agatha Hutabarat (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2025)
Diarrhea remains the leading cause of morbidity and mortality among infants in Indonesia, especially in areas with limited access to clean water and sanitation. This community service activity aims to improve mothers' understanding of the signs and symptoms of diarrhea in children, raise mothers' awareness of maintaining their children's hygiene and health to prevent diarrhea, and provide practical training on the initial treatment of diarrhea. The methods used include interactive lectures, group discussions, demonstrations on making oral rehydration solution (ORS), handwashing practice, and distribution of leaflets. The participants consisted of 30 mothers of young children in Bangun Rejo Village, Tanjung Morawa Subdistrict. Evaluation was conducted using pre-test and post-test knowledge assessments. The results of the activity showed a significant increase in mothers' knowledge regarding the prevention and management of diarrhea. Participants were able to identify diarrhea symptoms, practice making ORS, and were more prepared to take their children to healthcare facilities if dehydration signs were present. This activity demonstrated that community-based health education is effective in enhancing mothers' knowledge and preparedness in preventing diarrhea.